Relations of the KL Auschwitz Staff with the Civilians of Oświęcim and the Surrounding Area in the Years 1940–1945 - Kita, Agnieszka (Miasto i wojna, 2022)
The town of Oświęcim (German: Auschwitz) is invariably associated with the concentration and extermination camp that operated in its vicinity in the years 1940–1945. For many people, it comes as a surprise that during the war, in the shadow of the camp, a small garrison town functioned quite normally. It was an unusual town, considering that its original inhabitants – Poles and Jews – had been displaced, and the army that was stationed here was the SS garrison from KL Auschwitz. This paper aims to present the mutual relations between the civilian population (the remaining Poles, the settlers from the Reich, and the Volksdeutsche) and the SS men. How did they interact with each other? What restrictions and rules applied to their mutual relations? Why were the SS men not allowed to visit certain establishments? And why did the commandants devote so much attention in their orders to women? I have tried to find answers to the above-mentioned questions (and many more) in this paper. As my source base, I have predominantly used the orders of the commandant’s office (Kommandanturbefehle), the orders of the garrison commander (Standortbefehle), and the statements of civilians and former prisoners of the Auschwitz camp, all of which can be found in the Archives of the Auschwitz-Birkenau State Museum in Oświęcim.